2021
DOI: 10.1186/s40359-021-00584-9
|View full text |Cite
|
Sign up to set email alerts
|

Can use of pictograms reduce liquid medication administration errors by mothers? An interventional study

Abstract: Background Liquid medication dosing errors (LMDE) made by caregivers affect treatment in children, but this is not a well-studied topic in many low-and middle-income countries including in India. Methods An intervention study was conducted among mothers attending a pediatric outpatient clinic of a tertiary care setting in Ujjain, India. The mothers randomly measured 12 volumes of a paracetamol liquid preparation by using a dropper (0.5 and 1 mL), m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Several studies have shown promising interventions to help alleviate medication administration errors, including among patients and parents/guardians having limited health literacy levels. Medication errors can be minimized in parents/guardians with both lower and higher health literacy by using pictograms in addition to verbal medication counseling [35,36]. A study looking at delivering complex medication regimens for neonatal patients found that collaboration between parents/guardians, medical professionals, and manufacturers led to the creation of health literature and drug packaging that significantly decreased medication administration errors [37 ▪ ].…”
Section: Communicating Medication/dosing Instructionsmentioning
confidence: 99%
“…Several studies have shown promising interventions to help alleviate medication administration errors, including among patients and parents/guardians having limited health literacy levels. Medication errors can be minimized in parents/guardians with both lower and higher health literacy by using pictograms in addition to verbal medication counseling [35,36]. A study looking at delivering complex medication regimens for neonatal patients found that collaboration between parents/guardians, medical professionals, and manufacturers led to the creation of health literature and drug packaging that significantly decreased medication administration errors [37 ▪ ].…”
Section: Communicating Medication/dosing Instructionsmentioning
confidence: 99%
“…In addition, most of the respondents in the present study agreed that the usage of pictograms can reduce medication errors, which aligns with a study conducted by Patidar et al (2020). This study demonstrated that pictogram interventions reduced dosing errors among mothers with poor health literacy when administering liquid medication to children by approximately 48 to 54% and improved the mothers' understanding of dosing (Chan et al, 2015;Patidar et al, 2021). Therefore, pictograms are being utilized in patient counselling within pharmacy settings to enhance compliance and medication safety (Merks et al, 2021;Vaillancourt et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, most of the respondents in the present study agreed that the usage of pictograms can reduce medication errors, which aligns with a study conducted by Patidar et al (2020). This study demonstrated that pictogram interventions reduced dosing errors among mothers with poor health literacy when administering liquid medication to children by approximately 48 to 54% and improved the mothers' understanding of dosing (Chan et al, 2015;Patidar et al, 2021). Therefore, pictograms are being utilized in patient counselling within pharmacy settings to enhance compliance and medication safety (Merks et 139 al., 2021;Vaillancourt et al, 2019).…”
Section: Discussionmentioning
confidence: 99%